Glasgow Coma Scale and Its Components on Admission: Are They Valuable Prognostic Tools in Acute Mixed Drug Poisoning? - N. Eizadi Mood; A. M. Sabzghabaee; Gh. Yadegarfar; A. Yaraghi; M. Ramazani Chaleshtori (Critical Care Research and Practice)
Introduction. The verbal, eye, and motor components of Glasgow coma scale (GCS) may be influenced by poisoned patients' behavior in an attempted suicide. So, the values of admission GCS and its components for outcomes prediction in mixed drugs poisoning were investigated. Materials and Methods. A followup study data was performed on patients with mixed drugs poisoning. Outcomes were recorded as without complications and with complications. Discrimination was evaluated by calculating the area under the receiver operating characteristic curves (AUC). Results. There was a significant difference between the mean value of each component of GCS as well as the total GCS between patients with and without complication. Discrimination was best for GCS (AUC: 0.933±0.020) and verbal (0.932±0.021), followed by motor (0.911±0.025), then eye (0.89±0.028). Conclusions. Admission GCS and its components seem to be valuable in outcome prediction of patients with mixed drug poisoning.